2008
DOI: 10.1007/s12308-008-0006-8
|View full text |Cite
|
Sign up to set email alerts
|

Primary gastric T cell lymphoma mimicking marginal zone B cell lymphoma of mucosa-associated lymphoid tissue

Abstract: Primary gastric T cell lymphoma is rare and mostly of large cell type. In this paper, we present a case of gastric T cell lymphoma morphologically similar to the gastric marginal zone B cell lymphoma of mucosa-associated lymphoid tissue (MALT). Morphologically, the cells are small with abundant clear cytoplasm. Lymphoepithelial lesions are readily identified with diffuse destruction of gastric glands. Immunohistochemically, the neoplastic cells are CD3+/CD4+/CD8−/Granzyme B−. Molecular studies revealed monoclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The seven medium‐sized cell GTCL cases examined showed prolonged survival and a significantly better prognosis than nine large cell GTCL cases. Four previously reported medium‐sized cell GTCL cases 24,31,32,34 showed histological features reminiscent of mucosa‐associated lymphoid tissue (MALT)‐type B‐cell lymphoma, and three cases went into remission for 10 months to 3 years. It is suggested that medium‐sized cell GTCL is a distinct clinicopathological entity with categories of gastrointestinal as well as systemic T‐cell lymphoma.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The seven medium‐sized cell GTCL cases examined showed prolonged survival and a significantly better prognosis than nine large cell GTCL cases. Four previously reported medium‐sized cell GTCL cases 24,31,32,34 showed histological features reminiscent of mucosa‐associated lymphoid tissue (MALT)‐type B‐cell lymphoma, and three cases went into remission for 10 months to 3 years. It is suggested that medium‐sized cell GTCL is a distinct clinicopathological entity with categories of gastrointestinal as well as systemic T‐cell lymphoma.…”
Section: Discussionmentioning
confidence: 95%
“…Thirty‐four cases of primary GTCL were selected from 15 reports in the English literature from 1988 to 2007 8,9,21–34 . Histological evaluation was performed from the reported findings of surgical specimens in 27 of these cases and biopsy specimens in the remaining seven cases.…”
Section: Methodsmentioning
confidence: 99%
“…1,81,82 Epitheliotropism is seen in a minority of cases, particularly some examples of gastric T-cell lymphoma where the presence of lymphoepithelial lesions can mimic extranodal marginal zone lymphoma. 82,85 The immunophenotypic features also vary; some are CD4+, others are CD8+, and still others are CD4/CD8 double-negative. 1,81,82 Around half the cases express TCRb (Beta-F1), 81,82 and a subset can express TCRg or be TCR-silent.…”
Section: Epidemiologymentioning
confidence: 99%
“…Careful interpretation of the immunohistochemistry with additional clonality testing will solve such cases [52]. …”
Section: Pitfalls In Lymphoma Diagnosismentioning
confidence: 99%